Development of SYN-004, an oral beta-lactamase treatment to protect the gut microbiome from antibiotic-mediated damage and prevent Clostridium difficile infection. (October 2016) - Kaleko, Michael; Bristol, J. Andrew; Hubert, Steven; Parsley, Todd; Widmer, Giovanni; Tzipori, Saul; Subramanian, Poorani; Hasan, Nur; Koski, Perrti; Kokai-Kun, John; Sliman, Joseph; Jones, Annie; et al.
Abstract: The gut microbiome, composed of the microflora that inhabit the gastrointestinal tract and their genomes, make up a complex ecosystem that can be disrupted by antibiotic use. The ensuing dysbiosis is conducive to the emergence of opportunistic pathogens such as Clostridium difficile . A novel approach to protect the microbiome from antibiotic-mediated dysbiosis is the use of beta-lactamase enzymes to degrade residual antibiotics in the gastrointestinal tract before the microflora are harmed. Here we present the preclinical development and early clinical studies of the beta-lactamase enzymes, P3A, currently referred to as SYN-004, and its precursor, P1A. Both P1A and SYN-004 were designed as orally-delivered, non-systemically available therapeutics for use with intravenous beta-lactam antibiotics. SYN-004 was engineered from P1A, a beta-lactamase isolated from Bacillus licheniformis, to broaden its antibiotic degradation profile. SYN-004 efficiently hydrolyses penicillins and cephalosporins, the most widely used IV beta-lactam antibiotics. In animal studies, SYN-004 degraded ceftriaxone in the GI tract of dogs and protected the microbiome of pigs from ceftriaxone-induced changes. Phase I clinical studies demonstrated SYN-004 safety and tolerability. Phase 2 studies are in progress to assess the utility of SYN-004 for the prevention of antibiotic-associated diarrhea and Clostridium difficile disease. Highlights: Antibiotics (Abx) enter the intestines, cause dysbiosis and predispose to Clostridium difficile . SYN-004 is an orally delivered B-lactamase to degrade B-lactam Abx in the intestines. When given with an IV B-lactam Abx, SYN-004 degrades the Abx upstream of the colon. SYN-004 is not absorbed and does not alter systemic Abx levels. Canine and pig studies support Phase 2 clinical trials to prevent C. difficile .